STABLE ISOTOPE AND FLUID INCLUSION EVIDENCE FOR THE ORIGIN OF THE BRANDBERG WEST AREA SN-W VEIN DEPOSITS, NW NAMIBIA - Macey P.; Harris C. (My University, 2006)
The Brandberg West region of NW Namibia is dominated by poly-deformed turbidites and carbonate rocks of the Neoproterozoic Damara Supergoup, which have been regionally metamorphosed to greenschist facies and thermally metamorphosed up to mid-amphibolite facies by Neoproterozoic granite plutons. The meta-sedimentary rocks host Damaran-age hydrothermal quartz vein-hosted Sn-W mineralization at Brandberg West and numerous nearby smaller deposits. Fluid inclusion microthermometric studies of the vein quartz suggests that the ore-forming fluids at the Brandberg West mine were CO2-bearing aqueous fluids represented by the NaCl-CaCl2-H2O-CO2 system with moderate salinity (mean=8.6 wt% NaClequivalent). Temperatures determined using oxygen isotope thermometry are 415-521°C (quartz-muscovite), 392-447°C (quartz-cassiterite), and 444-490°C (quartz-hematite). At Brandberg West, the oxygen isotope ratios of quartz veins and siliciclastic host rocks in the mineralized area are lower than those in the rocks and veins of the surrounding areas suggesting that pervasive fluid-rock interaction occurred during mineralization. The O- and H-isotope data of quartz-muscovite veins and fluid inclusions indicate that the ore fluids were dominantly of magmatic origin, implying that mineralization occurred above a shallow granite pluton. Simple mass balance calculations suggest water/rock ratios of 1.88 (closed system) and 1.01 (open system). The CO2 component of the fluid inclusions had similar δ13C to the carbonate rocks intercalated with the turbidites. It is most likely that mineralization at Brandberg West was caused by a combination of an impermeable marble barrier and interaction of the fluids with the marble. The minor deposits in the area have quartz veins with higher δ18O values, which is consistent with these deposits being similar geological environments exposed at higher erosion levels. © Springer-Verlag 2006.
Keywords: BRANDBERG WEST; FLUID INCLUSIONS; NAMIBIA; STABLE ISOTOPES; TIN-TUNGSTEN; Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская